Comparing the course of anxiety in women receiving their first or repeated caesarean section: A prospective cohort study. Issue 3 (May 2020) - Schaal, N.K.; Fehm, T.; Wolf, O.T.; Gielen, P.; Hagenbeck, C.; Heil, M.; Fleisch, M.; Hepp, P.
Abstract: Background: Around 30% of births are through caesarean section and repetition rates for receiving a caesarean section are high. Aim: The aim of the prospective study was to compare the course of anxiety in women undergoing their first caesarean section and women experiencing a repeated caesarean section. Participants: 304 women with an indication for an elective caesarean section took part. 155 received their first caesarean section and 149 received a repeated caesarean section. Methods: In order to measure the course of anxiety on the day of the caesarean section subjective anxiety levels were measured and saliva samples for cortisol determination were taken at admission, during skin closure and two hours after the surgery. Blood pressure and heart rate were documented at skin incision and skin closure. Results: Women experiencing their first caesarean section displayed significantly higher anxiety levels compared to women with a repeated caesarean section. Scores of the STAI-State and visual analogue scale for anxiety differed significantly at admission ( p  = .006 and p  < .001) and heart rate and alpha amylase levels were significantly higher at skin closure ( p  = .027 and p  = .029). Conclusion: The results show that previous experience with a caesarean section has a soothing effect. The study aims to sensitize surgeons, anesthetists, nurses and midwives when treating women receiving a caesarean section and encourage them to incorporate soothing interventions, especially for women receiving their first caesarean section to reduce anxiety levels and consequently improve postoperative recovery and patients' satisfaction.